Synthesis and antitumour activity of some aryl semicarbazones - Pandeya S.N.; Yogeeswari P.; Sausville E.A.; Mauger A.B.; Narayanan V.L. (My University, 2025)
Various 4-substituted phenyl semicarbazone derivatives were synthesized and evaluated in vitro by NCI in the 3-cell line, one dose primary anticancer assay. Three compounds showed significant activity against breast MCF7 cell line and were further evaluated for potential anticancer activity in an in vitro human disease-oriented tumour cell line screening panel that consisted of 60 human tumour cell lines arranged in nine subpanels, representing diverse histologies. Leukemia, colon, ovarian and breast cancer cell lines were relatively more sensitive to these compounds than the other cell lines. The 4-carboxy substituted p-nitrobenzylidene phenyl semicarbazone (1c) emerged as the most active compound with average GI50 value (the molar drug concentration required for the 50% growth inhibition) of 28.6μM. This compound showed greater activity than methotrexate against NCI-H226(Lung), BT-549 and T-47D(Breast) cancer cell lines.